Pd/CNT catalysts for glycerol electro‐oxidation: Effect of Pd loading on production of valuable chemical products - Ahmad, M. S.; Cheng, C. K.; Kumar, Ravinder; Singh, Sharanjit; AL-japairai, Khater Ahmed Saeed; Ong, Huei Ruey; Hamidah, Abdullah; Khan, Maksudur R. (WILEY-VCH Verlag, 2020)
Glycerol (C3H8O3), a waste product of bio‐diesel, is considered as a suitable substrate for electro‐oxidation process to generate high value added products. In this work, palladium nanoparticles supported over activated MWCNTs with loadings of 5%‐40% were prepared using chemical reduction method and further employed to explore their potential for electro‐oxidation of glycerol to produce various high‐value‐compounds. The catalysts were characterized by physiochemical methods, such as X‐ray diffraction (XRD), Brunauer‐Emmett‐Teller (BET), and Transmission electron microscopy, while the electro‐oxidation activity of the catalysts was analysed using cyclic voltammetry (CV) and chronoamperometry (CA), and the products were identified by high performance liquid chromatography (HPLC). The electrochemical surface area (SESA) and mass activity (MA) were increased from 176.98 m2 g‐1 to 282.29 m2 g‐1 and 12.22 mA/mg to 49.53 mA/mg by increasing the Pd‐loading from 5% to 20%, respectively. While the further increase to 40% Pd loading, the SESA and MA values decreased to 231.45 m2 g‐1 and 47.63 mA/mg respectively. The results found that the optimum 20% Pd‐loading showed the excellent electrochemical properties due to exceptional distribution of Pd‐metal particles over MWCNTs. HPLC analysis showed the tartronic acid, glyceric acid and glyceraldehyde as dominant products. Mechanism of the reaction has also been proposed based on product distribution.